2019
DOI: 10.1029/2018jb017103
|View full text |Cite
|
Sign up to set email alerts
|

Noneruptive Unrest at the Caldera of Alcedo Volcano (Galápagos Islands) Revealed by InSAR Data and Geodetic Modeling

Abstract: Understanding volcanic unrest is crucial to forecasting eruptions. At active mafic calderas unrest culminates in eruption more frequently than at felsic calderas. However, the mafic caldera of Alcedo Volcano (Ecuador) has experienced repeated episodes of unrest without erupting, since at least 1992, when geodetic monitoring began. Here we investigate the unrest that occurred between 2007 and 2011 using interferometric synthetic aperture radar (InSAR) data and geodetic modeling. We observe an initial asymmetric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 69 publications
(129 reference statements)
3
36
1
Order By: Relevance
“…The uplift is classified as magma intrusion (Figure b) and is followed by a short period of rapid subsidence we attributed to local tectonic processes ( T ). This correlates well with the seismicity in the area observed by Davidge et al (), and the observations are consistent with the results of an InSAR and modeling study performed by Galetto et al (), which similarly identified intrusion and attributed the rapid episode of subsidence to rapid withdrawal and lateral magma migration.…”
Section: Resultssupporting
confidence: 91%
“…The uplift is classified as magma intrusion (Figure b) and is followed by a short period of rapid subsidence we attributed to local tectonic processes ( T ). This correlates well with the seismicity in the area observed by Davidge et al (), and the observations are consistent with the results of an InSAR and modeling study performed by Galetto et al (), which similarly identified intrusion and attributed the rapid episode of subsidence to rapid withdrawal and lateral magma migration.…”
Section: Resultssupporting
confidence: 91%
“…Based on previous research in the Galápagos Archipelago, the Cerro Azul volcano has an irregular soup-bowl-shaped caldera, and the younger structure here produced a type of caldera similar to those of other volcanoes in the western Galápagos, which have deep trapdoors and potential ring faults with surrounding radial rifts [6,14,16,20,43,73]. Above all, magma systems with small volumes and great depths occur in these structures [6,20,30]. According to the joint deformation model in Section 5.1, Cerro Azul tends to possess a peculiar structure with two composite causal deformation sources at the similar depth on Galápagos Archipelago.…”
Section: Conceptual Model For Unrest Eventmentioning
confidence: 80%
“…Repeated unrest events without eruption occurred in Alcedo from 1992 to 2011, where three of the events were all interpreted by the magma intrusion of platform-shaped sill deformation sources underground. A sill source model was adapted in the magma system, whose inflation was the origin of two events; the third was explained by the magma propagation from the current deflation sill to a new one [6]. The uplift event in the Fernandina volcano, on Fernandina Island, was presumed to be related to an inflation of a pipe-shaped magma chamber in 2012-2013 [46].…”
Section: Geological Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for a few other calderas, high resolution deformation time series spanning the last two or three decades are also available, providing a shorter but still valuable dataset. These resurgent calderas are felsic (Ischia, Italy; Long Valley, California; and Iwo Jima, Japan; Hill, 2006;Manzo et al, 2006;Ukawa et al, 2006;Ueda et al, 2018) or mafic (Sierra Negra and Alcedo; Galapagos) (Galetto et al, 2019, and references therein).…”
Section: Vertical Displacement At Resurgent Calderasmentioning
confidence: 99%